2016
DOI: 10.1128/aac.00641-16
|View full text |Cite
|
Sign up to set email alerts
|

p53 Mediates Colistin-Induced Autophagy and Apoptosis in PC-12 Cells

Abstract: Colistin is used as a last-line treatment option against multidrug-resistant (MDR) Gram-negative bacteria, which can cause life-threatening infections (1-3). However, its clinical use is limited by potential nephrotoxicity and neurotoxicity (4, 5), the mechanisms of which are still unknown. It has been discovered in a mouse model and neuroblastoma 2a cells that autophagy is involved in colistin-induced nephrotoxicity (6, 7). Apoptosis and autophagy are two common forms of cell death (8, 9). Apoptosis is a prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 51 publications
(62 reference statements)
1
16
0
Order By: Relevance
“…We further validated our model using two additional datasets generated in rat kidney proximal tubular (RPTC) cells 34 and rat adrenal medulla PC-12 cells 35 , respectively. Figure 3c shows the corresponding model predictions ( dashed curves ), which quantitatively reproduce the experimentally observed ( dots ) time courses of autophagy and apoptosis of RPTC cells in response to 20 μM cisplatin (ER stress-inducer).…”
Section: Resultsmentioning
confidence: 99%
“…We further validated our model using two additional datasets generated in rat kidney proximal tubular (RPTC) cells 34 and rat adrenal medulla PC-12 cells 35 , respectively. Figure 3c shows the corresponding model predictions ( dashed curves ), which quantitatively reproduce the experimentally observed ( dots ) time courses of autophagy and apoptosis of RPTC cells in response to 20 μM cisplatin (ER stress-inducer).…”
Section: Resultsmentioning
confidence: 99%
“…However, autophagy inhibition by p53 is more obvious when the nuclear localization sequence of p53 is deleted, leading to a merely cytoplasmic p53 localization (Ryan, 2011 ). In our present study, it is clear from the results that autophagy-related genes and protein were inhibited in colistin-treated PC-12-sip53 cells at 12 h, but opposite results occurred at 24 h, indicating that p53 down-regulated autophagy in PC-12-sip53 cells at 12 h and up-regulated autophagy at 24 h. Our previous study showed that colistin induced the highest expression levels of nuclear p53 after 12 h, but it induced the highest expression of cytoplasmic p53 at 24 h (Zhang et al, 2016 ). Thus, we inferred that the neurotoxicity of colistin acted as a stress/stimulation in PC-12 cells to be a signal of p53 translocation into the nucleus, as p53 expression levels was reduced by siRNA, leading to the lower levels of p53-translocated into nucleus, thereby silencing of p53 down-regulated colistin-induced autophagy in PC-12 cells for 12 h. Thereafter, cytoplasmic p53 plays a leading role in down-regulation of autophagy, while the relatively decreased cytoplasmic p53 level resulted in activation of autophagy in PC-12-sip53 cells at 24 h.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, understanding the complex functionality of autophagy induction is highly important. In our previous study, we proved that colistin (125 μg/mL) induces a high level of autophagy at 12 h and that autophagy can protect against the colistin-induced apoptosis (Jiang et al, 2014 ), and Zhang et al reported that colistin increased the expression level of p53, and p53 involved in colistin-induced autophagy and apoptosis (Zhang et al, 2016 ). In this follow-up mechanistic study, we are interested in exploring whether p53-mediated autophagy plays a cell survival role in colistin-treated PC-12 cells and p53 could act as a target gene to protect against colistin-induced neurotoxicity.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations